Monitoring The Seawater Intrusion Into Coastal Aquifer Using Geo-Electrical Sounding : A Case Study Of The Northern-Coastal Area Of Central Java, Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACT The aims of this study are : (1) to investigate whether there is seawater intrusion into the coastal-aquifer of the northern-coast of Central Java, (2) to study the seawater intrusion movement along the corresponding coastal area, particularly from the district of Brebes to the district of Kendal. To achieve the above goals, geo-electrical sounding technique was applied, hence by producing cross-sections of resistivity values which are perpendicular to the coast-line. The measurements were conducted in 1989 and 1996, each of wich included eleven locations which were at the same spot. Resistivity shown in the cross-section is the resistivity of the rock composition and the water in the aquifer. In this case, saline water has resistivity less than 1 ohm meter. The result shows that in 1989, among the eleven measured locations, there was only one location indicated interface between fresh water and saline seawater. This was at the cross section number 5 obtained in Pentalang. In 1996, there were 6 locations indicated the occurrence of interface. Connate saline water was detected at every cross section with various depth.